Stigmatization and self-perception in children with atopic dermatitis - Chernyshov PV (Dove Medical Press, 2016)
Pavel V Chernyshov Department of Dermatology and Venereology, National Medical University, Kiev, Ukraine Abstract: Atopic dermatitis (AD) is one of the most common skin diseases. Prevalence of AD is highest in childhood. Because of chronicity and often visible lesions, AD may lead to stigmatization and problems with self-perception. However, problems of self-perception and stigmatization in AD children are poorly studied. Literature data on general tendencies of children’s development, clinical course, and epidemiologic tendencies of AD in different age groups make it possible to highlight three main periods in the formation of self-perception and stigmatization. The first period is from early infancy till 3 years of age. The child’s problems in this period depend on parental exhaustion, emotional distress, and security of the mother–child attachment. The child’s AD may form a kind of vicious circle in which severe AD causes parental distress and exhaustion that in turn lead to exacerbation of AD and psychological problems in children. The second period is from 3 till 10 years of age. During this period, development of AD children may be influenced by teasing, bullying, and avoiding by their peers. However, the majority of children in this age group are very optimistic. The third period is from 10 years till adulthood. Problems related to low self-esteem are characteristic during this period. It is important to identify children with AD and their parents who need psychological help and provide them with needs-based consultation and care. Appropriate treatment, medical consultations, and educational programs may help to reduce emotional problems in AD children and their parents. Keywords: atopic dermatitis, stigmatization, self-perception, quality of life, children, pediatric dermatology, skin disease